Meio ambiente e cidadania: uma perspectiva sobre o desenvolvimento sustentável - Carmo, Wagner; Kroling, Aloisio; Maneia, Arismar (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
This article aims to show, from the art. 225 of the Federal Constitution of 1988, the responsibility of citizens in the process of planning, discussion and implementation of environmental policies. The starting point, here, is understand the words environment and citizenship. The focus is on art. 225 of the Brazilian Federal Constitution, which assigns to the State and the collective duty to preserve the environment, and the fact that, as a rule, the citizen declines of their obligation by assigning all responsibility only to the State. The proposal then is to develop ideas which include concepts, the role of society and the citizen and an indication of the effective tools which enable sustainable economic development with full involvement and participation of the State, legal persons and natural persons. The study concluded that the man needs to urgently rethink the moral values and its actions before the world, no longer mere receiver to be developer of right.